Packages go vertical. - Goldstein, H.
Stacking different chips in a package tucks a complete system into implantable devices like hearing aids. In this paper, the author describes how cell phones and wearable computers could be next
Keywords: Cell phones; Chip stacking; Hearing aids; Implantable devices; Integrated circuits; Vertical packaging; Wearable computers